A survey on the perception of health degree students on the use of Instagram and TikTok as learning tools - Silvia Garrido; Beatriz Losa; María Caballero; Alexandra Alvarez; Genny Raffaeli; Giacomo Cavallaro; Maria-Lorella Gianni; Felipe Garrido (Educación Médica)
Introduction: Limited academic literature has reviewed the usefulness of Instagram and TikTok, which degree students extensively use. Considering this gap, our research group has undertaken a study aimed at elucidating the perspectives of health sciences university students regarding the referred social media as learning tools. Methods: An online 23-question survey was distributed to undergraduate health sciences degree students across three Spanish universities. The questions were primarily related to the general usage of social media within the university educational environment, but they focused on Instagram and TikTok. Results: Students identified Instagram (68%) and YouTube (39%) as the most comfortable social networks for learning. Seventy-five percent of students indicated that they followed Instagram accounts about medicine or nursing, with 47% of these accounts lacking apparent university affiliations. One in three students followed TikTok accounts associated with medicine or nursing, with 63% of these accounts appearing to be non-university affiliated. Conclusions: Medical and nursing students are interested in seeking practical supplementary learning content from non-academic sources, particularly on the newest social networks like Instagram and TikTok. Improving the understanding of such content by university faculty can improve the guidance offered to students of such information. Resumen: Introducción: Existe una limitada literatura académica en relación con la utilidad de Instagram y TikTok, que sin embargo son muy utilizadas por los estudiantes de grado. Teniendo en cuenta esto, nuestro grupo de investigación ha llevado a cabo un estudio destinado a evaluar la percepción de los estudiantes universitarios de ciencias de la salud con respecto a las referidas redes sociales como herramientas de aprendizaje. Métodos: Se distribuyó una encuesta en línea de 23 preguntas a estudiantes de grado de ciencias de la salud de tres universidades españolas. Las preguntas estaban relacionadas principalmente con el uso general de las redes sociales en el entorno educativo universitario, pero se centraron en Instagram y TikTok. Resultados: Los estudiantes identificaron Instagram (68%) y YouTube (39%) como las redes sociales más cómodas para aprender. El 75% de los estudiantes indicó que seguía cuentas de Instagram sobre medicina o enfermería, y el 47% de estas cuentas carecían de afiliaciones universitarias aparentes. Uno de cada tres estudiantes seguía cuentas de TikTok asociadas con medicina o enfermería, y el 63% de estas cuentas parecían no estar afiliadas a la universidad. Conclusiones: Los estudiantes de medicina y enfermería están interesados en buscar contenido práctico complementario de aprendizaje en fuentes no académicas, en particular en las redes sociales más nuevas como Instagram y TikTok. Mejorar la comprensión de dicho contenido, en particular por parte del profesorado universitario, puede mejorar la orientación ofrecida a los estudiantes de dicha información.